2006
DOI: 10.1212/01.wnl.0000242756.00084.f9
|View full text |Cite
|
Sign up to set email alerts
|

African American women have poor long-term survival following ischemic stroke

Abstract: Compared with whites and men, African American women have a lower 1-year survival following ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…These results were partly confirmed by expanding the dataset with more recently acquired patients and looking at short-term results, demonstrating the same trend toward poorer functional outcome, although higher mortality did not manifest for this shorter time. This finding, plus Qureshi et al's 12 report of higher long-term mortality (without baseline matching, however), suggests that longer term factors may be more important than short-term recovery to survival for black women after stroke. The consequences of a much higher incidence of diabetes mellitus could be one such factor.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…These results were partly confirmed by expanding the dataset with more recently acquired patients and looking at short-term results, demonstrating the same trend toward poorer functional outcome, although higher mortality did not manifest for this shorter time. This finding, plus Qureshi et al's 12 report of higher long-term mortality (without baseline matching, however), suggests that longer term factors may be more important than short-term recovery to survival for black women after stroke. The consequences of a much higher incidence of diabetes mellitus could be one such factor.…”
Section: Discussionmentioning
confidence: 67%
“…5 Although blacks bear a disproportionate burden of stroke incidence and stroke-related morbidity and mortality, [6][7][8][9][10][11] clarification of the role of race in influencing rtPA outcomes has been hampered by small numbers of non-white patients in randomized controlled trials. Qureshi et al 12 have shown long-term mortality for black women was highest among a cohort of blacks and whites. However, the differences in baseline factors, such as stroke severity or differences in subtype, could have explained the higher longer term mortality within this study.…”
mentioning
confidence: 99%
“…While some authors have found better survival after initial admission with stroke5 and acute myocardial infarction (AMI),6 others, in contrast, have found poor survival after initial admission with AMI7 among ethnic minority groups. Similar inconsistent results have also been reported among the USA ethnic groups 811. However, many of these studies were either based on localised populations5 7 11 or short-term in their follow-up 7 10.…”
mentioning
confidence: 57%
“…For example, in the National Institute for Neurological Disorders and Stroke (NINDS) tPA trial, African American women had the highest 1-year mortality when compared with white men, white women and African American men. 30 It might, therefore, be inappropriate to generalize outcomes to all women if only one race-ethnic group is represented.…”
Section: Discussionmentioning
confidence: 99%